2020
DOI: 10.1038/s41586-020-3020-3
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Chern number in quantum anomalous Hall insulators

Abstract: The quantum anomalous Hall (QAH) state is a two-dimensional topological insulating state that has quantized Hall resistance of h/Ce 2 and vanishing longitudinal resistance under zero magnetic field, where C is called the Chern number 1,2 . The QAH effect has been realized in magnetic topological insulators (TIs) 3-9 and magic-angle twisted bilayer graphene 10,11 . Despite considerable experimental efforts, the zero magnetic field QAH effect has so far been realized only for C = 1. Here we used molecular beam e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
114
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(124 citation statements)
references
References 33 publications
4
114
5
1
Order By: Relevance
“…It can be used to build heterostructures to study exotic topological states, such as topological magnetoelectric effect, axion insulator and high-Chern-number insulator. [47,48] Nevertheless, the apparent distinct behavior of the doped samples in comparison to the pure ones suggests that further theoretical considerations are required for a full understanding.…”
Section: Discussionmentioning
confidence: 99%
“…It can be used to build heterostructures to study exotic topological states, such as topological magnetoelectric effect, axion insulator and high-Chern-number insulator. [47,48] Nevertheless, the apparent distinct behavior of the doped samples in comparison to the pure ones suggests that further theoretical considerations are required for a full understanding.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ] Furthermore, it was suggested that the topologically protected 1D hinge state of 3D SOTIs sheds new light on the development of novel electronic applications based on Majorana bound states and surface quantum anomalous Hall effect, such as topological quantum computers and chiral circuit interconnects. [ 18 , 19 ] However to date, few realistic materials have been identified experimentally as 3D SOTIs. [ 18 , 20 ] A natural question to ask is whether a broad class of 3D SOTIs can be found experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…The band-gap in a Chern insulator can be as small as 10 meV for silicene with transition metal adatoms [97] or as large as 340 meV for stanene honeycomb lattices in which one sublattice is passivated by halide atoms, whilst the other sublattice is not [98]. For E gap ∼ 10 meV, the high temperature limit is 18.5 K, whilst for E gap ∼ 340 meV, the high temperature limit is much larger at 627 K. The ferromagnetic transition temperature is typically of the order of milli-Kelvins [80,99] or a few Kelvins [100], though ferromagnetic transitions as high as T = 243 K (for passivated stanene) and T = 509 K (for passivated germanene) have also been predicted [98]. If the ferromagnetic transition temperature T f is larger than E gap /(2πk B ), we can imagine setting the Chern insulators at a temperature larger than E gap /(2πk B ) but still lower than T f so that the Casimir-Lifshitz energy is again dominated by the zero (Matsubara) frequency contribution, for which the Hall conductivity is quantized and the longitudinal conductivity vanishes; correspondingly, the force can be made repulsive.…”
Section: Casimir Repulsion Between Chern Insulatorsmentioning
confidence: 99%